O003 Longitudinal associations of obstructive sleep apnea and sleep macroarchitecture with future cognitive function in middle-aged and older men from a community-based cohort study. (9th November 2022) - Parker, J; Vakulin, A; Melaku, Y; Wittert, G; Martin, S; D'Rozario, A; Catcheside, P; Lechat, B; Teare, A; Toson, B; Appleton, S; Adams, R
Abstract: Study objectives: Prospective studies examining associations of obstructive sleep apnea (OSA) and sleep macroarchitecture with future cognitive function remain limited to older participants, many with baseline cognitive impairment, which may be a confounder. This study examined OSA and sleep macroarchitecture predictors of cognitive function (visual attention, processing speed, and executive function) after 8–10 years in community-dwelling middle-aged and older men. Methods: Of 433 Florey Adelaide Male Ageing Study participants who underwent home-based polysomnography (2010–2011), 157 completed baseline and follow-up cognitive testing. Trail-making tests A (TMT-A) and B (TMT-B) were administered at baseline (2007–2010) and follow-up (2018–2019) examinations. Linear regression analyses examined associations of OSA and sleep macroarchitecture with cognitive task performance adjusted for baseline demographic, biomedical, and behavioural factors and cognitive performance, with sleep macroarchitecture models additionally adjusted for the apnea-hypopnea index (AHI). Results: At baseline, participants were mean (SD) aged 58.9 (8.9) years with normal cognition. OSA prevalence (AHI ≥10/h) was 52.9%, with severe OSA (AHI ≥30/h) in 9.6%. Following covariate adjustment, higher N1 sleep (%) was associated with better TMT-A performance at follow-up (B= -0.04, 95% CI [-0.06, -0.01], p=0.003), whereas higher mean oxygen saturation was associated with worse TMT-A performance at follow-up (B=0.11, 95% CI [0.02, 0.19], p=0.012). Conclusions: In this sample of community-dwelling middle-aged and older men, N1 sleep % and mean oxygen saturation showed independent associations with visual attention and processing speed after 8–10 years. Further longitudinal studies remain warranted to determine whether finer-grained sleep microarchitecture parameters identify individuals at risk of future cognitive dysfunction.